Pengaruh Struktur Kepemilikan Saham, Struktur Modal dan Profitabilitas Pada Nilai Perusahaan - Apriada, Kadek; Suardikha, Made Sadha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this study to determine the effect of  institutional ownership, managerial ownership, capital structure, and profitability on firm value . The data used in the form of external secondary data from the Indonesia Stock Exchange 2011-2012 period with observations made on 82 manufacturing companies. The sampling technique used was purposive sampling with predetermined criteria. The data analysis technique used is the Linear Regression analysis using       SPSS 17. Based on the results of Regression linear  analysis showed  that institutional ownership has a positive effect on firm value. When the higher institutional ownership, then external control will be the stronger on firm . The presence of institutional ownership will encourage more optimal control on the performance of the company in achieving corporate goals is to optimize the value of the company.
Keywords: Keywords: institutional ownership, managerial ownership, capital structure, profitability, firm value